UJI ANGKA LEMPENG TOTAL BAKTERI TERHADAP IKAN CAKALANG ASAP YANG DIRENDAM DENGAN LARUTAN SAYURAN KUBIS - Mohamad, Fihrina; Mohamad, Yolanda Pransiska (JOURNAL HEALTH AND NUTRITIONS, 2016)
ABSTRACT Test the Total Plate Number (ALT) and more precisely ALT mesophyll aerobics or anaerobic mesophyll using solid media with the end result in the form of colonies that can be observed visually in the form of numbers in colony (cfu) per ml or per gram or colony / 100ml. Skipjack is one of the mainstay fishery commodities from Maluku waters and is excellent, as indicated by the still low utilization rates, such as the management of small-scale and traditional fisheries. The ensiling process is the result of fermentation of cabbage vegetables using NaCl salt solution (Asnadi 2009). One of the preservation processes that use natural ingredients is the ensiling process. The ensiling process is a process of preserving natural foods (fish, crops, meat, etc.)This study aims to determine the total bacterial plate number of smoked skipjack soaked in cabbage vegetable solution The method used in the study was an experiment with the treatment of boiling cabbage vegetables by testing the total bacterial plate number. The sample used in this study is the fungus caklang fish which are as many as 3 tails. Data analysis used to calculate the number of bacterial cultures that grow on Nutrient Agar media using Coloni Counter. By using the formula: Number of colonies x 1 / diluent factor.Results of the study: there is a difference in the amount of the total number of bacterial plates in smoked skipjack which is soaked in a solution of vegetable cabbage. On immersion treatment for 1 hour. the number of bacteria is 1.7 x 105 CFU / gram. in the treatment of soaking for 2 hours. the number of bacteria was 2.5 x 105 CFU / gram, in the immersion treatment for 3 hours. Obtained from the calculation of the number of bacteria is 2.1 x 105 CFU / gram. In testing the control treatment of smoked skipjack, it was found that the number of bacteria was 8.6 x 102. When viewed from the average number of bacteria in the treatment the overall sample was still below the SNI standard (5 x 102) microbial pollution in smoked food. ABSTRAK Uji Angka Lempeng Total (ALT) dan lebih tepatnya ALT aerob mesofil atau anaerob mesofil menggunakan media padat dengan hasil akhir berupa koloni yang dapat diamati secara visual berupa angka dalam koloni (cfu) per ml atau per gram atau koloni/100ml. Ikan cakalang merupakan salah satu komoditas perikanan andalan dari perairan Maluku dan menjadi primadona, ditunjukkan oleh tingkat pemanfaatan masih rendah, seperti pengelolaan usaha perikanan berskala kecil dan bersifat tradisional. Proses ensiling adalah hasil fermentasi sayuran kubis menggunakan larutan garam NaCl (Asnadi 2009). Salah satu proses pengawetan yang menggunakan bahan alami adalah proses ensiling. Proses ensiling merupakan proses pengawetan pangan alami (ikan, hasil tanaman, daging, dll)Penelitian ini bertujuan untuk mengetahui angka lempeng total bakteri terhadap ikan cakalang asap yang direndam dengan larutan sayuran kubis Metode yang digunakan dalam penelitian adalah eksperimen dengan perlakuan pendaman sayuran kubis dengan uji angka lempeng total bakteri. Sampel yang digunakan pada penelitian ini adalah ikan caklang asap yang sebanyak 3 ekor. Analisis data yang digunakan Untuk menghitung jumlah biakan bakteri yang tumbuh pada media Nutrient Agar dengan menggunakan Coloni Counter. Dengan menggunakan rumus : Jumlah koloni x 1/faktor pengencer.Hasil penilitan : ada perbedaan jumlah antara jumlah angka lempeng total bakteri pada ikan cakalang asap yang direndam deng larutan sayuran kubis. Pada perlakuan perendaman selama 1 jam. jumlah bakterinya adalah 1,7 x 105 CFU/gram. pada perlakuaan perendaman selama 2 jam. jumlah bakteri adalah 2,5 x 105 CFU/gram, pada perlakuan perendaman selama 3 jam. Diperoleh dari perhitungan jumah bakteri adalah 2,1 x105 CFU/gram. Pada pengujian perlakuan kontrol pada ikan cakalang asap didapati jumlah bakteri 8,6 x 102. Jika dilihat dari rata-rata jumlah bakteri pada perlakuan sampel keseluruhan masih dibawah standar SNI (5 x 102) pencemaran mikroba pada bahan pangan yang diasap.